2021
DOI: 10.1186/s12870-021-03133-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis reveals regulatory network and regulators associated with proanthocyanidin accumulation in persimmon

Abstract: Background Proanthocyanidins (PAs) are important plant secondary metabolites that confer flavor, nutritional value, and resistance to pathogens. Persimmon is one of the PA richest crops. Mature fruits can be inedible because of the astringency caused by high PA levels and need to go through a de-astringency treatment before consumption. The molecular basis for PA accumulation is poorly known, particularly transcriptional regulators. We characterised three genotypes (‘Luotiantianshi’ (LT), ‘Mopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 89 publications
1
19
0
Order By: Relevance
“…The theoretical basis for the synthesis and accumulation of saponins in different tissues of tea plants is still not clear. With the development of high-throughput sequencing (HTS) technologies, the synthetic pathways of many secondary metabolites in varieties of plants have been elucidated [ 16 , 17 ]. In this study, the saponin content of tea leaves, flowers and seeds in different growth periods was determined.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical basis for the synthesis and accumulation of saponins in different tissues of tea plants is still not clear. With the development of high-throughput sequencing (HTS) technologies, the synthetic pathways of many secondary metabolites in varieties of plants have been elucidated [ 16 , 17 ]. In this study, the saponin content of tea leaves, flowers and seeds in different growth periods was determined.…”
Section: Introductionmentioning
confidence: 99%
“…5C ). Studies have shown that hormone- and transcription-related genes both perform functions in flavonoid accumulation ( Rai et al, 2016 ; Zheng et al, 2021a ; Zheng et al, 2021b ). In this work, we found that plant hormone signal transduction and flavonoid biosynthesis may play important roles in the color formation of D. cirrhosa tubers, and there may be a close relationship between these two biological processes in regulating PA synthesis in D. cirrhosa .…”
Section: Resultsmentioning
confidence: 99%
“…Certain fruits, such as the persimmon, have both high- and low-CT varieties. Low-tannin fruits stop generating CTs at a primary stage of growth, whereas tannin-rich fruits accumulate them until they are fully matured, imparting an unpleasant flavor ( Zheng et al., 2021 ). Despite a wealth of research on the compounds and amounts of tannins in commercially important fruits, only a few species have been studied to see how they change as the fruit matures.…”
Section: Tanninsmentioning
confidence: 99%